Kerupuk Kulit Ikan Pari Sebagai Alternatif Peningkatan Pendapatan Rumah Tangga Di Karundang Kota Serang - Deni sunaryo (Universitas Serang Raya, 2019)
Stingray Skin Crackers As An Alternative To Increase Household Income In Karundang Serang CityDeni SunaryoJurusan Manajemen, Universitas Serang Raya Email: denisunaryomm@gmail.comAbstractOne of the potentials of the Karundang sub-district in Cipocok Jaya District, Serang City, is processing stingrays, while the processing of stingrays is only taken from the meat while the skin of stingrays and stingray bones is used as waste. The nutritional value of larger stingray waste so that it is able to produce added value from that value becomes a useful value and added value for both the residents and the surrounding environment.The service program carried out on March 15, 2019, at one of the posts of the Karundang Village community activity in the Cipocok Jaya sub-district, Serang City. The number of participants who participated in this activity were 16 local residents. The training process is carried out by introducing stingray skin raw material that is still fresh (not yet rotten), fire resistant or not easily torn, has a thickness of at least 0.5 mm, left and right easily damaged. As well as simple processing materials for cooking and packaging. In this activity the servant asked for information related to the service activities of the processing of stingray skin into crackers both in terms of activities and presenters in expressing activities.This service program supports residents with enthusiasm and respect for this activity and provides advice for the next service activity, which is making abon from stingray skin.Keywords: stingray skin waste, income.